What about - the natural world? :miles kelly publishing - Williams, Brian (Miles Kelly Thaxted, 2011)
"The Natural World" is an engaging children's book that explores the beauty and diversity of nature. It covers various ecosystems, including forests, oceans, deserts, and wetlands, introducing young readers to the plants and animals that inhabit each environment.